2019
DOI: 10.4025/actascianimsci.v41i1.46483
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort and grazing behavior of Girolando heifers in integrated crop-livestock (ICL) and crop-livestock-forest (ICLF) systems

Abstract: To compare the integrated crop-livestock-forest (ICLF) and crop-livestock (ICL) systems in relation to thermal comfort and grazing behavior of Girolando heifers, a 2 × 2 crossover trial (two system and two periods) was carried out with eight ¾ Holstein × ¼ Gyr heifers in Xaraés–palisade grass pasture under intermittent stocking with 10 days of occupation period and 20 days of resting. In ICLF, crown cover of eucalyptus planted in rows was 65% at the beginning of the experiment. Animal behavior was assessed thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…However, they are below the range of 40-70 bites.min -1 reported for growing cattle (Delagarde et al, 2001). The daily TB (Table 3) was similar to the values of 9,865 to 11,159 bites found by Suárez et al (2014) in beef steers grazing hybrid grass B. ruziziensis × B. decumbens × B. brizantha mulato II (CIAT 36087) in a tropical region of Colombia. These values are considered low, since cattle can perform more than 35,000 prehension actions during the day (Carvalho et al, 2001;Werner et al, 2019).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…However, they are below the range of 40-70 bites.min -1 reported for growing cattle (Delagarde et al, 2001). The daily TB (Table 3) was similar to the values of 9,865 to 11,159 bites found by Suárez et al (2014) in beef steers grazing hybrid grass B. ruziziensis × B. decumbens × B. brizantha mulato II (CIAT 36087) in a tropical region of Colombia. These values are considered low, since cattle can perform more than 35,000 prehension actions during the day (Carvalho et al, 2001;Werner et al, 2019).…”
Section: Resultssupporting
confidence: 70%
“…Previously, Souza et al (2019) observed that heifers in ICLF spent more time grazing than those in ICL during the day (from 6:00 to 18:00h). This fact seems to be related to the thermal comfort offered by the trees' shade, since the number of daily grazing sessions and the duration of the grazing sessions did not differ (P<0.05) between systems (ICL vs. ICLF) (Table 3).…”
Section: Resultsmentioning
confidence: 95%
“…Additionally, the cows in that study had access to a shaded area, which would affect the preference for grazing during the daytime. In another study, we also found that, during the daytime, dairy heifers spend more time grazing in a silvopastoral when compared to heifers in pasture with full sun condition (Souza et al, 2019).…”
Section: Resultsmentioning
confidence: 61%
“…Grazing behavior was accessed by bioacoustic methodology (Souza et al, 2019) using MP3 audio recorders adapted to the cow's halters to register the sounds of grazing, ruminating, and resting on the 17 th and 18 th day of the experimental period. The audio was continuously recorded for 48 hours, and the time spent for each activity during the nighttime (from 18:00 to 5:59) and the daytime (from 6:00 to 17:59) was quantified by the Audacity ® software (Free Software Foundation, Boston, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Under heat challenge, cows have a higher motivation to seek water (McDonald et al, 2020), shaded areas (Cardoso et al, 2021), ventilated areas (Vieira et al, (2021b) or sprinklers areas (Chen et al, 2013). Animals raised in areas without shade visit the water trough more frequently than animals raised on SPS (Vizzotto et al, 2015;de Souza et al, 2019;Giro et al, 2019;Vieira et al, 2020;De-Sousa et al, 2021a). Giro et al (2019) found that beef cows raised on silvopasture system has a 23% lower frequency of visits to a water trough in than cows in treeless pasture.…”
Section: Cattle Behaviourmentioning
confidence: 99%